2018
DOI: 10.1002/ange.201802833
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion‐Assisted Polymerization‐Induced Hierarchical Self‐Assembly of Giant Sea Urchin‐like Aggregates on a Large Scale

Abstract: Hierarchical solution self-assembly has become an important biomimetic method to prepare highly complex and multifunctional supramolecular structures.H owever,d espite great progress,i ti ss till highly challenging to prepare hierarchical self-assemblies on al arge scale because the selfassembly processes are generally performed at high dilution. Now,anemulsion-assisted polymerization-induced self-assembly (EAPISA) method with the advantages of in situ selfassembly,s calable preparation, and facile functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…reported a facile method to synthesize ACPs by the robust, efficient, and orthogonal click chemistry under mild reaction conditions . Our group also synthesized a serial of amphiphilic ACPs through the click reactions of amine-epoxy/amine-thiol and the obtained ACPs could self-assemble into various architectures, such as nanotubes, vesicles, and sea urchin like assemblies . In addition, some of them were used as electrode materials. , Thus, we want to use this facile method of thiol-epoxy/amine-epoxy click reactions to further design and synthesize ACPs with excellent biocompatibility and stimulus-responsive properties for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…reported a facile method to synthesize ACPs by the robust, efficient, and orthogonal click chemistry under mild reaction conditions . Our group also synthesized a serial of amphiphilic ACPs through the click reactions of amine-epoxy/amine-thiol and the obtained ACPs could self-assemble into various architectures, such as nanotubes, vesicles, and sea urchin like assemblies . In addition, some of them were used as electrode materials. , Thus, we want to use this facile method of thiol-epoxy/amine-epoxy click reactions to further design and synthesize ACPs with excellent biocompatibility and stimulus-responsive properties for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the reaction media of PISA can be water, alcohol and nonpolar solvents, which have been extensively investigated by Armes [ 110 ], Boyer [ 111 ], Charleux [ 112 ], Pan [ 113 ], An [ 114 ], and others [ 115 , 116 , 117 ]. For examples, Zhou et al reported that PISA strategy, with the advantages of in situ self-assembly, scalable preparation, and facile functionalization, can be used to prepare hierarchical multiscale sea urchin-like assemblies, taking advantage of epoxy thiol click polymerization [ 118 ]. The PISA process enables the effective preparation of nanostructures with varies morphologies starting with a single initial solvophilic homopolymer and extend the chain via one-pot reactions.…”
Section: Basic Concepts Related To Supramolecular Chiralitymentioning
confidence: 99%
“…The average wall thickness of the hollow polymeric spheres measures 87 ± 35 nm. It was found in the previous studies that alternating copolymers could self-assemble into various ordered nanostructures, including nanotubes, 29 sea urchin-like self-assemblies, 30 nanospheres, 31 and vesicles. 32,33 To the best of our knowledge, the hollow spheres observed in this work represent the first example in the self-assembly of alternating copolymers.…”
mentioning
confidence: 99%
“…Self-assembly of amphiphilic copolymers in solution has been considered as a versatile approach for the preparation of various ordered nanostructures. Among different types of polymer precursors, alternating copolymers exhibit a unique alternating monomeric unit structure in the backbone. This allows the self-assembly of alternating copolymers into nanostructures with hydrophobic or hydrophilic domains of uniform dimension in spite of the dispersity of the copolymers. By taking advantage of the peculiarity of alternating copolymers, we developed the first template-free method toward porous HCSs with uniform micropores in the wall, by the self-assembly of an amphiphilic alternating copolymer in solution (Figure ). Driven by hydrophobic, π–π, and H-bonding interactions, the alternating copolymer, P­(BGF- a -DHBDT), self-assembled into HPSs of narrow size distribution in a solvent mixture of DMF and H 2 O.…”
mentioning
confidence: 99%